The effect of fish oil enema in ethanol induces colonic damage in rats - Hakan YÜCEYAR; Ömer ÖZÜTEMİZ and A. HÜSEYİNOV and Murat ALKANAT and Serhat BOR and Çiğdem DİNÇER and Ahmet ÇOKER and Yücel BATUR (Turkish Journal of Gastroenterology, 2019)
-